Double Literacy, Double Protection?: Minimising Gen Z's Risky Digital Credit Behaviour In Surabaya Through Financial Literacy And Digital Financial Literacy - Fabian Benediktus; Cliff Kohardinata (UNIVED Press, 2024)
This study aims to investigate the credit risk issues that Generation Z is facing In Surabaya, particularly digital credit and loans. This study utilises a closed-ended questionnaire to explore Generation Z’s knowledge and awareness of subjective financial literacy, digital financial literacy, and risky credit behaviour, so that the results can reveal the influence of subjective financial literacy and digital financial literacy on risky credit behaviour controlled by gender and financial condition of Generation Z in Surabaya. To the best of the researcher’s knowledge, there are no studies that specifically highlight the influence of subjective financial literacy and digital financial literacy on risky credit behaviour. Based on the results of the multiple linear regression approach, researchers found that subjective financial literacy and digital financial literacy have a significant positive effect on risky credit behaviour, which means that the higher the subjective financial literacy and digital financial literacy, the riskier credit behaviour is minimized, gender has no significant effect on risky credit behaviour, financial condition has a significant negative effect on risky credit behaviour.